EGFR-Targeted Therapeutics: Focus on SCCHN and NSCLC. (2008) - Sattler, Martin; Abidoye, Oyewale; Salgia, Ravi
Abstract : Cancers of the head and neck and of the lung are associated with high morbidity and mortality rates that have remained relatively unchanged for more than 3 decades, despite advances in radiation therapies and chemotherapies over the same time. It is generally believed that the efficacy of standard therapy regimens has reached a plateau for these cancers. The discovery of specific aberrant molecular signaling pathways in solid tumors has afforded promising new directions for newer "targeted" cancer therapeutics. Among these, the epidermal growth factor receptor (EGFR) shows promise as a therapeutic target. Clinical studies have demonstrated that this targeted approach provides clinically meaningful benefit. This article reviews EGFR-targeted therapies in use and in development, with a focus on the role of EGFR in the pathophysiology of head and neck and lung cancer, and new concepts being investigated to improve outcomes with these agents.